The economics of the Common Market - Swann, Dennis (Harmondsworth : Penguin Books, 1975)
The book describes the social and political origins of the common market, traces its evolution through the practical decisions that have been taken since 1958, and indicates the possibilities of future development
Includes index.
Bibliography: p. [251]-255.
osc 05/11/2018
Loans
Keywords: Common Markets; Economic integration